DHT-receptor in cultured human fibroblasts: binding study in a family with androgen insensitivity (complete testicular feminisation). Issue 5 (October 1982) - Donti, E; Nicoletti, I; Filipponi, P; Venti, G; Bocchini, V; Santeusanio, F
Abstract : 3H-DHT binding was examined in cultured skin fibroblasts from a patient with complete testicular feminisation (CTF), from his heterozygote mother, and his clinically normal sister, who menstruated normally. Binding parameters were: Bmax less than 1 fmol/mg protein and KD unmeasurable in CTF; Bmax = 24 fmol/mg protein and KD = 3.63 X 10(-9) mol/l in the mother; and Bmax = 46 fmol/mg protein and KD = 3.7 X 10(-9) mol/l in the sister. Five cultures obtained from genital and non-genital skin of normal male and female subjects were used as controls, in which Bmax ranged from 37 to 62 fmol/mg and KD from 2.0 to 3.6 X 10(-9) mol/l. The considerable reduction of Bmax in the obligate heterozygote and the normal binding capacity in the sister, a probable heterozygote, suggests that it may be possible to use the DHT-receptor assay to identify carriers in families with androgen resistance.